Evaluation of the Quality Indicators of the Drug "Bralekord" Solution for Infusions (Global Journal of Medical Research, 2023)
The results of standardization and quality control of the drug "Bralecord" solution for infusions are given, according to such quality indicators as: description, authenticity, transparency, color, pH, mechanical inclusions, impurities, osmolality.
Keywords: quality indicators; standardization; quality control; injection solution; pharmacopoeia; normative document